Cost-Effectiveness Analysis Based on Intelligent Electronic Medical Arthroscopy for the Treatment of Varus Knee Osteoarthritis. (7th May 2021) - Liu, Chunfeng; Wang, Zhen; Liu, Jinlian; Xu, Yaozeng
Abstract : The incidence of inverted knee osteoarthritis is slowly increasing, there are technical limitations in the treatment, and the operation is difficult. In this article, we will study the benefits and costs of arthroscopic cleaning treatments based on intelligent electronic medicine. This article focuses on knee osteoarthritis patients in the EL database. There are 12 male patients, accounting for 66.67%, and 6 female patients, accounting for 33.33%. The average body mass index (BMI) of the patients was 28.08, the average time from first knee discomfort to surgery was 28.44 months, and the average time of arthroscopic debridement treatment for patients with VKOH knee osteoarthritis was 143.11 minutes. One case of perioperative complication occurred within 35 days after operation, which was a soleus muscle intermuscular venous thrombosis. After immobilization and enhanced anticoagulation for 1 week, it was stable without risk of shedding. The average postoperative study time was 20.00 months. The electronic medical arthroscopy cleaning treatment plan in this article can greatly improve the quality of life of patients and can check the pathological state in time, with low cost. In the course of treatment, comprehensive treatment costs can be saved by 45%. Arthroscopic clean-up treatment can not only reduce knee pain and other uncomfortable symptoms, restore normal knee joint function, and improve the quality of life of patients, but also correct the unequal length of the lower limbs, thereby avoiding spinal degeneration caused by knee instability. Therefore, it is the first choice for the treatment of advanced knee osteoarthritis in patients with VKOH.